A survey on MANET intrusion detection - Mandala, Satria; Ngadi, Md. Asri; Abdullah, A. Hanan (Computer Science Journals, 2008)
In recent years, the security issues on MANET have become one of the primary concerns. The MANET is more vulnerable to be attacked than wired network. These vulnerabilities are nature of the MANET structure that cannot be removed. As a result, attacks with malicious intent have been and will be devised to exploit these vulnerabilities and to cripple the MANET operation. Attack prevention measures, such as authentication and encryption, can be used as the first line of defense for reducing the possibilities of attacks. However, these techniques have a limitation on the effects of prevention techniques in general and they are designed for a set of known attacks. They are unlikely to prevent newer attacks that are designed for circumventing the existing security measures. For this reason, there is a need of second mechanism to â€œdetect and responseâ€? these newer attacks, i.e. â€œintrusion detectionâ€?. This paper aims to explore and to classify current techniques of Intrusion Detection System (IDS) aware MANET. To support these ideas, a discussion regarding attacks, IDS architectures, and researches achievement on MANET are presented inclusively, and then the comparison among several researches achievement will be evaluated based on these parameters. By this way, several existing security problems on MANET can be probed quickly for future researches.